Analysis of Islamic Comsumption Theory on Demand For Fast Moving Consumer Goods (FMCG) - Alkhonsa, Fitria; Nurwahidin, Nurwahidin (UI Scholars Hub, 2023)
This study aims to measure how Muslim consumers have applied Islamic Consumption Theory to regularly consumed products by analyzing the variables of maslahah, final spending, and tawazun Islamic consumption theory against the demand for Fast Moving Consumer Goods (FMCG). Fourty FMCG consumers can be removed in this study and were distributed randomly. The sample was done change to collected with a purposive sampling method, which obtain the primary data in the form of the respondents' answers to the distributed questionnaires. The results indicate an influence of maslahah in Islamic Consumption Theory on FMCG demand, while the other two variables of final spending and tawazun did not affect FMCG demand. The determination coefficient test result shows that FMCG demand can be explained through maslahah, final spending, and tawazun by 68.3%. On contrary, the remaining 31.7% (100% -68.3%) is influenced by other variables which not included in this study